Prevalence of developmental dental anomalies in pediatric patients and an assessment of students' knowledge in two mexican dental schools : a cross-sectional study = Prevalencia de anomalías del desarrollo dental en pacientes pediátricos y evaluación del conocimiento de estudiantes de dos facultades de odontología mexicanas : un estudio transversal - Castro Rodríguez, Estefanía Montserrat
Dental anomalies (DAs) in children refer to conditions affecting the structure, number, shape, and size of teeth. This study aimed to assess the prevalence of these anomalies in both primary and permanent dentitions among two Mexican pediatric populations aged 2-14 years. Additionally, the level of knowledge about DAs among students pursuing a degree in dentistry in both universities was determined. A cross-sectional study was conducted on children making their first visit to the Pediatric Dental Clinics of the Universities of Nuevo León and San Luis Potosí in México between March and May 2017. The prevalence of DAs was estimated. In addition, a questionnaire comprising 20 closed items regarding DAs was administered to 100 undergraduate students to evaluate their level of knowledge. Ninety-four children (54 boys and 42 girls; mean age 9.73±2.1 years) were included. Twenty-two patients (23.4%) exhibited at least one DA in their primary or permanent teeth. The most common DAs were in size (macrodontia) and structure (enamel hypoplasia). Agenesis occurred three times, and there were two cases of mesiodens. Regarding gender, 10 patients were girls (45.4%), and 12 were boys (54.6%). The prevalence of DAs in permanent teeth (57.5%) was higher than that in primary teeth (42.5%, p=0.031). Only two patients presented DAs in both primary and permanent teeth. No tooth-shaped anomalies were detected. Regarding the level of knowledge among the university students, the percentage of correct answers was 61.6%. Our findings emphasize the importance of encouraging parents to initiate pediatric dental visits early. Additionally, the study highlights the significance of conducting a thorough evaluation of the patients.